Neuropsychological assessment and quality of life in patients with refractory temporal lobe epilepsy related to hippocampal sclerosis - Mantoan,Marcele Araujo Silva (2006)
INTRODUCTION: Epilepsy is a disorder that results in abnormal activity in a group of neurons that may have significant impact on the normal cognitive processes and behavior. Temporal lobe epilepsy (TLE) is the most frequent form of partial epilepsy in adults, and hippocampal sclerosis (HS) the most common neuropathologic finding in patients with medically refractory TLE. Patients with TLE often present cognitive difficulties that may be determined by the effects of epileptic discharges and side of the lesion. And its consequence is that patients have poor effects on quality of life (QOL). PURPOSE: We report the relationship between neuropsychological assessment and QOL under the hypotheses that patients with worst results in neuropsychological assessment have poorer QOL assessed by the QOLIE-31. RESULTS: Regarding seizure frequency, 23 (46%) had had 1-5, 20 (40%) 6-10 and 7 (14%) more than 10 seizures/month. In relation to seizure types, 5 (10%) had had auras, 37 (74%) complex partial seizures and 8 (16%) partial evolving to generalized tonic-clonic seizures (GTCS). Neuropsychological evaluation had a positive correlation with QOLIE-31 domains. QOL evaluations had the worst scores in QOLIE-31 were in Cognitive Function (45.0) and Social Function (46.0). The best was Overall QOL (62.0). CONCLUSION: People with epilepsy have great impact on their QOL not only because of daily seizures but because of the impact seizures cause in their cognitive functions. TLE is an example of how refractory epilepsy can exterminate any possibilities of work, study and live in a society that discriminates someone with epilepsy who also presents cognitive decline.